Community effectiveness of copepods for dengue vector control: systematic review - Lazaro, Adhara; Han, W. W.; Manrique‐Saide, P.; George, L.; Velayudhan, R.; Toledo, J.; Runge-Ranzinger, Silvia; Horstick, Olaf (Tropical medicine & international health, 2015)
Vector control remains the only available method for primary prevention of dengue. Several interventions exist for dengue vector control, with limited evidence of their efficacy and community effectiveness. This systematic review compiles and analyses the existing global evidence for community effectiveness of copepods for dengue vector control.